Chaos Synergy, Geopolitics And Culture Explain History Of International Relations. A Critique of William Wohlforth - B. F. Martynov (Vestnik MGIMO-Universiteta)
The article is a critique of William Wohlforth’s piece on usefulness of IR theory in explaining the history of international relations published in this issue of MGIMO Review of International Relations. It offers an alternative answer to the key question raised by Wohlforth – why humans continue to resort to such a self-destructive method of conflict resolution as war. The author argues that the current aggravation of relations between Russia and the West helps find a new way of answering this eternal question. With the help of historical examples and logical reasoning the author shows that international relations are governed not so much by structural anarchy, as Wohlforth argues, as by «natural spontaneous systemic force», which does not depend on the will of people and manifests itself in events that seem random and irrational. This force can be rationally known by studying how classical geopolitics, cultural (especially legal culture) and civilizational factors influence international relations. These aspects, according to the author, explain both the Cold War and its on-going «second edition». Taking into account civilizational, cultural, historical, linguistic and legal characteristics of actors becomes the key to an adequate understanding of international politics. It should also be noted that cultural and civilizational features affect not only the practice of international relations, but also the IR. According to the author, the theory of political realism in Russia has been reinterpreted in light of the maxim: «God is not in power, but in truth». Thus, an important category of Russian realism turns out to be «justice».The alternative answer to the question about the recurrent practice of wars in international relations can be formulated as follows: the states are sometimes forced to fight each other due to their geopolitical contradictions complicated by cultural and civilizational differences.